Implementasi Program Beasiswa Genius S1 Dalam Mengatasi Kesenjangan Pendidikan Tingkat Sarjana di Kabupaten Bojonegoro - wati, Diah Rahma; Agus Satmoko Adi (Universitas Negeri Surabaya (Unesa), 2024)
Education is the right of every Indonesian child, so it is appropriate to provide guarantees to fulfill the learning process in an inclusive manner. The economic capabilities that tend to differ in the Bojonegoro region have an impact on the number of graduates, resulting in differences or gaps in education between regions. This gap can hamper the equal distribution of the quality of undergraduate education in Bojonegoro Regency. The Genius S1 Scholarship provides a solution in the form of undergraduate education assistance for all Bojonegoro residents who are studying at a university in Bojonegoro. The aim of this research is to describe the implementation of the Genius S1 Scholarship program in overcoming the undergraduate level education gap in Bojonegoro Regency and to review whether this program has been effective in overcoming the undergraduate education gap in Bojonegoro Regency. This research uses a qualitative approach with descriptive methods. Data was collected using observation techniques, in-depth interviews and documentation. Informants in this research were selected using key informants. The results of this research show that the undergraduate genius scholarship program has been implemented in accordance with applicable SK and SOP. The Genius S1 Scholarship Program is implemented by providing tuition assistance with certain conditions and an administrative selection process, interviews, skills tests and field surveys so that it can be right on target.